Implementasi Remote Laboratorium Praktikum Infrastruktur LAN Pada Masa Work From Home - Indriyanta, Gani; Agus Haryono, Nugroho; Beny Waluyo, Prihadi (Technomedia Journal, 2023)
The Covid19 pandemic demands creativity in teaching LAN Infrastructure practicum. The limitations of meetings conducted online require skills improvement training for students. Network simulators and emulator programs have several disadvantages when compared to the direct use of network devices. The implementation of the LAN Infrastructure Practicum Laboratory during the Work From Home Period can already be tested in the Informatics Study Program of Duta Wacana Christian University. The implementation of remote network devices to support the LAN Infrastructure practicum is made by utilizing the available internet network. Connecting devices from anywhere are possible using Open-VPN so that students seem to be present in person in the laboratory and can access available network devices. Device trials can already be carried out to access 12 Cisco routers, 5 Mikrotik routers, and 12 access points. The beneThe benefit rate of remote labs from a student point of view is 62,5%. Smooth access from home to remote labs is only 70% due to network constraints.